2013
DOI: 10.1111/hdi.12074
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arterial microcalcification of the vascular access on cardiovascular mortality in hemodialysis patients

Abstract: Gross vascular calcification seen on imaging studies is common in hemodialysis (HD) patients, and is a significant predictor for cardiovascular mortality in HD patients. We have reported that arterial microcalcification (AMiC) of the vascular access is associated with increased aortic stiffness. This study investigated the impact of vascular access AMiC on cardiovascular mortality in HD patients. The study included 149 HD patients (mean age: 59.1 ± 13.9 years, 86 men and 63 women, 65.8% diabetic) who underwent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 31 publications
(51 reference statements)
0
14
0
Order By: Relevance
“…Another study reported that arterial microcalcification was associated with 1-year primary unassisted patency in a retrospective cohort of 114 patients (51). The same group showed that microcalcification also predicts cardiovascular mortality in patients on hemodialysis (52). In conclusion, the available data are inconsistent with respect to the effect of vascular calcification on AVF outcomes, indicating that larger and multicenter studies are needed to finally answer this question.…”
Section: Vascular Calcification and Avf Outcomesmentioning
confidence: 98%
“…Another study reported that arterial microcalcification was associated with 1-year primary unassisted patency in a retrospective cohort of 114 patients (51). The same group showed that microcalcification also predicts cardiovascular mortality in patients on hemodialysis (52). In conclusion, the available data are inconsistent with respect to the effect of vascular calcification on AVF outcomes, indicating that larger and multicenter studies are needed to finally answer this question.…”
Section: Vascular Calcification and Avf Outcomesmentioning
confidence: 98%
“…[12][13][14]19 In this study, a mean diabetic duration >10 years yielded a survival detriment for subgroups I and II vs a similar subcontrol group, suggesting the pivotal role of long standing diabetes as a cofactor for increased mortality in patients with upper extremity Vc.…”
Section: Discussionmentioning
confidence: 53%
“…Notably, diabetic patients had a 3.43-fold risk of arteriovenous access Vc compared with nondiabetic patients. Similarly, Yun et al 19 showed that upper arm arterial microcalcification evident in spot vascular access specimens (radial or brachial artery) obtained intraoperatively in hemodialysis patients (65.8% diabetic patients) increased cardiovascular mortality by 2.35-fold. Apart from upper extremity vascular access level, all-cause mortality rates were increased 16-fold in patients with AMC of pelvic or femoral arteries (7% diabetic patients) compared with patients with no Vc (3% diabetic patients).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Therefore, elderly patients, especially those with multiple comorbidities, may not survive long enough to obtain the benefits of AVF placement. In other words, AVG can be considered to be the first choice of VA for elderly patients with multiple comorbidities and limited life expectancy although, in the general population, AVG is considered to be a secondary choice due to its lower patency and association with increased patient morbidity and mortality, or as an alternative option in cases with unsuitable, damaged, or sometimes exhausted veins inappropriate for AVF access creation [18][19][20] . The association between increased age and greater risk of maturation failure may be due to the absence of adequate vessels, which are essential components for successful AVF creation, as vessels naturally deteriorate with age and are also damaged by concurrent comorbidities.…”
Section: Discussionmentioning
confidence: 99%